Implementation of Hadith in Contemporary Islamic Law: A Case Study of The Determination of Fatwa Law in the Exchange of New Money Ahead of Eid in Indonesia - Marita Kaniawati; Siti Saidah Muthmainah; Lani Herliana (Riviera Publishing, 2025)
Diabetes mellitus is a chronic metabolic disease with a growing prevalence and mortality rate globally and nationally. Conventional treatment is effective but has limitations such as side effects and high cost. Therefore, phytotherapy is an alternative that is increasingly in demand as a complementary therapy. This study aims to evaluate the clinical evidence of various natural ingredients used as complementary therapies for type 2 diabetes mellitus. A systematic review was conducted on original research articles on humans from 2020–2025 obtained from Google Scholar. Of the 209 articles, 13 met the inclusion criteria. Data were analyzed descriptively including plant type, preparation form, research design, and influence on blood glucose levels. Moringa leaves (Moringa oleifera) are the most studied plants and show a consistent effect of lowering blood glucose. Other plants such as bitter melon, binahong leaves, kersen leaves, jicama, brown and black rice, and herbal combinations also provide significant hypoglycemic effects. The natural ingredients reviewed show potential as a safe and evidence-based complementary therapy in the management of type 2 DM. However, further research with a more rigorous design is needed to guarantee its effectiveness and safety